Iris surface features and anterior chamber depth in Chinese adolescents - Chen-Wei Pan (BMC Ophthalmology, 2020)
Abstract Background We aim to determine the association of iris surface features including crypts, color and contraction furrows with anterior chamber depth (ACD) in a school-based sample of Chinese teenagers. Methods Totally, 2346 students aged 13 to 14 years in Mojiang located in the Southwestern part of China contributed to this analysis. Iris surface features were graded based on standardized slit-lamp photographs. Ocular biometric parameters including ACD were measured using an IOL Master. Generalized estimating equation was incorporated in the linear regression models to assess the relationship between iris surface features and ACD. Results A significant trend of increasing ACDs with more contraction furrows were observed. On average, the mean ACD was 3.03 mm in participants with contraction furrows of grade 1 while it was 3.10 mm in those with grade 3 (mean difference, 0.07 mm, P = 0.01). Adjusting for other potential confounders such as gender, height and weight did not significantly changed the associations. Compared with individuals with contraction furrows of grade 1, those with grade 3 had a greater ACD of 0.06 mm (95% confidence interval: 0.01, 0.11) in multivariate-adjusted model. There were no significant relationships between ACD and iris crypts or color. (P > 0.10). Conclusions More iris contraction furrows are associated with greater ACDs while the association with iris color and crypts were not significant.